PENGARUH STUDENT TEAMS ACHIVEMENT DIVISION TERHADAP PEROLEHAN BELAJAR PEMBELAJARAN ILMU PENGETAHUAN SOSIAL SEKOLAH DASAR - Dara Parujad, Clara Oktapiani; Marzuki, Marzuki; Sugiyono, Sugiyono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is purpose to analyze the influence of student teams achievement division toward the result of study and how much that influence the student teams achievement division on learning outcome of social science in class V Elementary School 33 Pontianak Utara. The method used is an experiment with quasi experimental design¸with the form of nonequivalent control group design. The population and sample of this research are all students af class V Elementary School 33 Pontianak Utara, consist of two classes with totaling 56 students. Based on data analysis the average results of posttest experimental class were 84.41 and control class posttest was 79.74. Obtained tcount (4.92) and ttable 1.6749, because of tcount> ttable, so Ha was accepted. The conclusion that there is an effect of student teams achievement division social toward the learning outcome in social science in class V of the Elementary School 33 Pontianak Utara. Based on the calculation of the effect size obtained Δ = 0.76, categorized as medium. Thus, student teams achievement division has a positive influence on the lerning achievement of students in learning social science class V in Elementary School 33 Pontianak Utara.Keywords: Effective, Student Teams Achievement Divisions, Learning Outcomes, Learning Social Science.